Description of Genetic Variants in BRCA Genes in Mexican Patients with Ovarian Cancer: A First Step towards Implementing Personalized Medicine - Delgado Balderas, Jesús Rolando; Garza Rodríguez, María de Lourdes; Gómez Macías, Gabriela Sofía; Barboza Quintana, Álvaro; Barboza Quintana, Oralia; Cerda Flores, Ricardo Martín; Miranda Maldonado, Ivett C.; Vazquez Garcia, Hugo Mauricio; Valdez Chapa, Lezmes Dionicio; Antonio Macedo, Mauro; Dean, Michael; Barrera Saldaña, Hugo Alberto (Molecular Diversity Preservation International, 2018)
Abstract Gynecologic cancers are among the leading causes of death worldwide, ovarian cancer being the one with the highest mortality rate. Olaparib is a targeted therapy used in patients presenting mutations in BRCA1 and BRCA2 genes. The aim of this study was to describe BRCA1 and BRCA2 gene variants in Mexican patients with ovarian cancer. Sequencing of BRCA1 and BRCA2 genes from tumors of 50 Mexican patients with ovarian cancer was made in a retrospective, non-randomized, and exploratory study. We found genetic variants in 48 of 50 cases. A total of 76 polymorphic variants were found in BRCA1, of which 50 (66%) had not been previously reported. Furthermore, 104 polymorphic variants were found in BRCA2, of which 63 (60%) had not been reported previously. Of these polymorphisms, 5/76 (6.6%) and 4/104 (3.8%) were classiﬁed as pathogenic in BRCA1 and BRCA2, respectively. We have described the genetic variants in BRCA1 and BRCA2 of tumors from Northeast Mexican patients with sporadic ovarian cancers. Our results showed that the use of genetic testing helps recognize patients that carry pathogenic variants which could be beneﬁcial for personalized medicine treatments. Keywords: BRCA; ovarian cancer; personalized therapy; sequencing